2022
DOI: 10.1111/camh.12613
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a guided paced breathing audiovisual intervention on anxiety symptoms in Palestinian children: a pilot randomized controlled trial

Abstract: BackgroundChildren in Palestine may be at high risk for anxiety symptoms. However, access to mental health services is limited. Therefore, the objective of this study was to conduct a pilot randomized controlled trial to examine whether a guided audiovisual paced breathing intervention was feasible, acceptable, and improved anxiety symptoms in Palestinian children.MethodsStudents (6–10 years old) in an after‐school program in Palestine were randomly assigned to the intervention or control condition. All partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The whole Palestine region, and the Gaza Strip in particular, have undergone a persistent conflict for decades that has implied repetitive exposure to violence and war, and that have clearly eroded the psychological well-being, health, and quality of life of children population (D'Andrea et al, 2023;Manzanero et al, 2021;Massad et al, 2009;Shank et al, 2023;Shehadeh et al, 2015;Thabet et al, 2014Thabet et al, , 2009Thabet & Thabet, 2016;Thabet & Vostanis, 1999, 2000, adding urgency to the need to understand and address the implications of war-related trauma in this population.…”
Section: The Case Of the Gaza Stripmentioning
confidence: 99%
“…The whole Palestine region, and the Gaza Strip in particular, have undergone a persistent conflict for decades that has implied repetitive exposure to violence and war, and that have clearly eroded the psychological well-being, health, and quality of life of children population (D'Andrea et al, 2023;Manzanero et al, 2021;Massad et al, 2009;Shank et al, 2023;Shehadeh et al, 2015;Thabet et al, 2014Thabet et al, , 2009Thabet & Thabet, 2016;Thabet & Vostanis, 1999, 2000, adding urgency to the need to understand and address the implications of war-related trauma in this population.…”
Section: The Case Of the Gaza Stripmentioning
confidence: 99%
“…A pilot randomized clinical trial found that a guided paced breathing audiovisual intervention of no more than 10 min per session decreased anxiety symptoms in the intervention group compared to the control group (Shank et al., 2022). Another study evaluating a self‐help, online programme showed improvements in anxiety symptoms in children and adolescents, and reductions in life interference in children (Rowe, Evans, Donovan, Spence, & March, 2023).…”
mentioning
confidence: 99%